Integrative genomic analysis identifies a role for intercellular adhesion molecule 1 in childhood asthma. Issue 2 (6th January 2014) - Klaassen, Ester M. M.; van de, Kim D. G.; Jöbsis, Quirijn; Penders, John; van, Frederik Jan; Quaak, Marieke; den, Gertjan J. M.; Koppelman, Gerard H.; van, Constant P.; van, Guillaume; Dompeling, Edward
Abstract Background Childhood asthma is characterized by chronic airway inflammation. Integrative genomic analysis of airway inflammation on genetic and protein level may help to unravel mechanisms of childhood asthma. We aimed to employ an integrative genomic approach investigating inflammation markers on DNA, mRNA, and protein level at preschool age in relationship to asthma development. Methods In a prospective study, 252 preschool children (202 recurrent wheezers, 50 controls) from the Asthma DEtection and Monitoring (ADEM) study were followed until the age of six. Genetic variants, mRNA expression in peripheral blood mononuclear cells, and protein levels in exhaled breath condensate for intercellular adhesion molecule 1 (ICAM1), interleukin (IL)4, IL8, IL10, IL13, and tumor necrosis factor α were analyzed at preschool age. At six years of age, a classification (healthy, transient wheeze, or asthma) was based on symptoms, lung function, and medication use. Results The ICAM1 rs5498 A allele was positively associated with asthma development (p = 0.02) and ICAM1 gene expression (p = 0.01). ICAM1 gene expression was positively associated with exhaled levels of soluble ICAM1 (p = 0.04) which in turn was positively associated with asthma development (p = 0.01). Furthermore, rs1800872 and rs1800896 in IL10 were associated with altered IL10 mRNA expression (p < 0.01). Exhaled levels of IL4, IL10, and IL13 were positively associated with asthma development (p < 0.01). Conclusions In this unique prospective study, we demonstrated that ICAM1 is associated with asthma development on DNA, mRNA, and protein level. Thus, ICAM1 is likely to be involved in the development of childhood asthma.